The house of Wolves - Patterson, James, 1947-; Lupica, Mike (New York : Little, Brown and Company, 2023)
The Wolfs, the most powerful family in California, have a new head-thirty-six-year-old former high school teacher Jenny Wolf. That means Jenny now runs the prestigious San Francisco Tribune. She also controls the legendary pro football team, the Wolves. And she hopes to solve her father's murder.
Keywords: Fathers -- Fiction; Daughters -- Fiction; Murder -- Fiction; Families -- Fiction; Newspaper publishing -- Fiction; Football teams -- Fiction; Families; Fathers; Football teams; Large type books; Murder; San Francisco (Calif.) -- Fiction; California -- Fiction; California; California -- San Francisco; Detective and mystery fiction; Fiction; Large type books; Detective and mystery fiction